2008
DOI: 10.1097/tp.0b013e318187758b
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Impaired Aerobic Capacity on Liver Transplant Candidates

Abstract: Peak VO2 is severely impaired in candidates for LT and affects survival and post-LT course. Perioperative respiratory rehabilitation programs validated in lung and heart transplantation must be tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
122
0
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(133 citation statements)
references
References 33 publications
5
122
0
6
Order By: Relevance
“…Dharancy et al (24) demonstrated that majority of the cirrhotic patients presents lower peak O 2 values than the expectation. Moreover, Epstein et al verified that class A patients from the Child-Pugh Score presented better peak O 2 values when compared to the individuals from the groups B and C (25) .…”
Section: Discussionmentioning
confidence: 99%
“…Dharancy et al (24) demonstrated that majority of the cirrhotic patients presents lower peak O 2 values than the expectation. Moreover, Epstein et al verified that class A patients from the Child-Pugh Score presented better peak O 2 values when compared to the individuals from the groups B and C (25) .…”
Section: Discussionmentioning
confidence: 99%
“…5) u pacjentów z marskością wątroby badanie ergospirometryczne jest na pierwszej pozycji jako badanie, które pozwala ocenić nie tylko wydolność wysiłkową, ale również odpowiedź chronotropową. Poszczególne parametry ergospirometrywiąże się ze zwiększonym ryzykiem zgonu u pacjentów po przeszczepieniu wątroby [17][18][19]. Również w badaniu ergospirometrycznym obserwuje się nieprawidłowości u pacjentów z HPS [20].…”
Section: Sercowo-płucny Test Wysiłkowyunclassified
“…The exercise capacity of subjects with hepatic cirrhosis was assessed using oxygen consumption on maximum cardiopulmonary tests on fifteen different articles (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). These studies are described on table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Taking together the studies that have assessed patients with hepatic cirrhosis before and after transplantation, two of them (28,29) found a positive association between increases in aerobic capacity and chance of survival post transplantation. On the other hand, in another study (31) it was concluded that patients that who underwent hepatic transplantation presented greater exercise capacity after the surgery.…”
Section: Exercise Capacity Before and After Hepatic Transplantationmentioning
confidence: 99%